Dietary supplementation with algae and polyphenols in rabbit male: Effects on semen quality traits - Vizzarri , Francesco; Palazzo , Marisa M.; Casamassima , Donato; Corino , Carlo; Chiapparini , Sara; Ondruska , Lubomir; Knizatova, Nikola; Massanyi , Martin; Tirpak , Filip; Massanyi , Peter (Annales Universitatis Paedagogicae Cracoviensis Studia Naturae, 2018)
In recent years, many studies have been focused on natural substances that can affect health of animals. A mix of different extracts was used as dietary supplement and it consists exclusively of natural products. Its main components are polyphenols from terrestrial and marine origins and plant polysaccharides. The effect of this supplement on reproduction has not been reviewed in the past what is a reason why its effect on the reproduction potential of male rabbits was tested. The aim of the present study is to determine effects of natural mix during 120-days long in vivo experiment on selected reproductive traits of male rabbits. Natural mix was supplemented in two different concentrations (T1 - 0.3% and T2 - 0.6%) with the basal ingredients of the conventional rabbit feed in pellet form. In our experiments, emphasis was placed on both the spermatozoa concentration and its motility parameters as well as on the properties of seminal plasma and antioxidant activity. The dietary supplementation with the natural extracts mix positively altered the quality traits of rabbit spermatozoa, but these changes were statistically not significant. In experimental T1 group a significant increase of GPx and FRAP content, both regarding the antioxidant markers profile in seminal plasma was recorded. We can conclude that the supplementation of 0.3% of natural mix did not significantly negatively affect any of the studied reproductive parameters of male rabbits, but some improvement in several antioxidant parameters was found.